Analisis Sosial Pernikahan Dini di Desa Batumarta VI - Ais Surasa; Abdillah Manan (Al Fuadiy Jurnal Hukum Keluarga Islam, 2024)
In general, marriage is a very sacred procession carried out by two people between a man and a woman to commit to living together in a legal bond. Marriage as an activity unites two human beings legally according to religion and the State. Not only an ordinary activity, this activity is also seen as the longest worship in life which can be a storehouse of rewards. In the Quran there is also a discussion about marriage not only once or twice mentioned, but several times. Marriage for mankind is important and is a human nature determined by the almighty creator, because with marriage a person will get a balance of life both biologically, psychologically and socially. However, the age of marriage that is too young can result in many things, the welfare in the family becomes vulnerable and can increase divorce cases due to lack of awareness of responsibility in married life. The method used in this research is qualitative research (field riseach), data collected through observation, interviews and documentation. Data analysis techniques, data reduction, data presentation and drawing conclusions. Some cases of early marriage also occur in Batumarta VI village, Madang Suku III sub-district, East OKU Regency in the last few years marriages have been dominated by early marriages, the impact of early marriage is that the age of marriage that is only as old as corn experiences various kinds of problems from economic factors, domestic violence (domestic violence) and divorce, the factor of disharmony and lack of family education is what causes bad conditions to occur.